Warm-up stretches reduces sensations of stiffness and soreness after eccentric exercise - Reisman, S.; Walsh, L. D.; Proske, U. (Medicine & Science in Sports & Exercise, 2005)
Purpose: A commonly used method for warm-up before exercise is to stretch muscles. How this benefits performance remains uncertain. After a period of eccentric exercise, there is muscle damage accompanied by an increase in passive tension, perceived as a sensation of increased stiffness in the exercised muscles. We have tested the idea that warm-up stretches might reduce levels of passive tension to reduce sensations of stiffness and soreness after eccentric exercise.